Short Communication Mechanism of Monocarpic Senescence of Momordica dioica: Source-Sink Regulation by Reproductive Organs (Biological Sciences - PJSIR, 2005)
Average chlorophyll levels of male ) plants alongwith defruited plants of Momordica dioica were higher than female ( + ) plants or monoecious plants. The order of senescence was as follows: + > monoecious > > defruited. Protein content in the leaves and dry weight of aerial plant parts remained higher in  as compared to defruited, + and monoecious plants. Evidently, the absence of fruit was noted to delay senescence.